Trends in vascular access among patients on hemodialysis; a nationwide survey from Egypt - Eman Nagy; Karem Salem; Mostafa Abdelsalam; Rasha Shemies; Nehal Elshabrawy; Ahmed M. Abd Elwahab; Alaa Sabry; Alaa A. Elsawi; Ahmed Albeyaly; Hamed Eleraky; Hala Mahmoud; Mohamed Elsayed; et al. (BMC Nephrology)
Abstract Problem statement Vascular Access (VA) in hemodialysis (HD) patients is vital for treatment efficiency and is influenced by Egypt’s healthcare system and socioeconomic factors. It is a complex issue, shaped by both challenges and opportunities within the nation’s healthcare infrastructure. Aim To examine trends in VA use and associated characteristics in patients on HD based on data from a nationwide survey in Egypt. Methods This cross-sectional study targeted patients on maintenance hemodialysis across Egypt, using stratified cluster sampling from 11 representative governorates. Medical personnel collected data using a structured electronic Google Form questionnaire, which gathered data on patient demographics, clinical details, VA creation and complications, and healthcare access. Results The study included 3,582 chronic HD patients. Data were collected over a one-year period from May 2023 to May 2024. An arteriovenous fistula (AVF) was the initial VA for 669 patients (18.7%), while a temporary catheter was used as the initial access in 2,861 patients (79.9%). AVF thrombosis was the primary cause of AVF failure, occurring in 69.7% of cases. Pre-HD VA creation was associated with substantially better fistula maturation, fewer VA numbers, and lower VA-related complications. Conclusion Significant regional and sociodemographic variations in VA practices were observed across Egypt. The findings revealed persistent reliance on temporary catheters at HD initiation, with encouraging but limited progress in pre-HD AVF planning. These trends underscore the need for early referral strategies and targeted interventions to optimize vascular access outcomes nationwide.